Use of Event-Based Traffic Data in Generating Time–Space Diagrams for Evaluation of Signal Coordination. Issue 1 (January 2014) - Zheng, Jianfeng; Liu, Henry X.; Misgen, Steve; Schwartz, Kevin; Green, Bob; Anderson, Mike
The time–space (TS) diagram is a popular visualization tool in evaluating progression quality for signalized arterials, and most signal optimization software products (such as Synchro) can generate TS diagrams as part of the optimization output. During the signal retiming process, TS diagrams generated by optimization software need to be validated by field observations, and minor changes will be made to signal control parameters if a discrepancy is observed. The validation process is time-consuming and costly. Through the use of high-resolution event-based traffic data collected from existing traffic signal controllers, a practical procedure for constructing TS diagrams for signalized arterials is proposed. The diagrams can be used as a convenient visualization tool in evaluating the performance of traffic signals and in identifying opportunities for fine-tuning in a timely manner. Reasonable agreement was found between the TS diagram and vehicle trajectory data collected from the field. A field experiment was carried out to illustrate how signal parameter changes could be made by intuitive evaluation of the TS diagram. Recommendations and limitations of the proposed approach are discussed.